2022
DOI: 10.1101/gr.276196.121
|View full text |Cite
|
Sign up to set email alerts
|

HDAC9structural variants disruptingTWIST1transcriptional regulation lead to craniofacial and limb malformations

Abstract: Structural variants (SVs) can affect protein-coding sequences as well as gene regulatory elements. However, SVs disrupting protein-coding sequences that also function as cis-regulatory elements remain largely uncharacterized. Here, we show that craniosynostosis patients with SVs containing the Histone deacetylase 9 (HDAC9) protein-coding sequence are associated with disruption of TWIST1 regulatory elements that reside within HDAC9 sequence. Based on SVs within the HDAC9-TWIST1 locus, we defined the 3'-HDAC9 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…We report the fourth case of CS and deletion involving HDAC9 without disrupting the TWIST1 -coding region. Recently, Hirsch et al (2022) showed that SVs involving HDAC9 disrupt TWIST1 -regulatory elements within HDAC9 in patients with CS. Our patient had coronal synostosis that was also described in two of the previously reported patients with deletion and one with a translocation breakpoint disrupting the HDAC9–TWIST1 locus ( Hirsch et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We report the fourth case of CS and deletion involving HDAC9 without disrupting the TWIST1 -coding region. Recently, Hirsch et al (2022) showed that SVs involving HDAC9 disrupt TWIST1 -regulatory elements within HDAC9 in patients with CS. Our patient had coronal synostosis that was also described in two of the previously reported patients with deletion and one with a translocation breakpoint disrupting the HDAC9–TWIST1 locus ( Hirsch et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…CNVs residing in regulatory regions (enhancers and promoters) and long non-coding RNA can modulate gene expression of OP-related genes. In a comprehensive study by Hirsch et al, structural variations in HDAC9 gene that influenced the transcription of the neighbouring TWIST1 gene were discovered in craniosynostosis patients [ 40 ]. Deletions in HDAC9 gene, but not in the TWIST1 protein-coding sequence, caused development of craniosynostosis.…”
Section: Cnvs In Regulatory Regions Can Modulate Gene Expression Of O...mentioning
confidence: 99%
“…Deletions in HDAC9 gene, but not in the TWIST1 protein-coding sequence, caused development of craniosynostosis. Regulatory elements that reside in the HDAC9 gene contributed to the transcriptional regulation of the neighbouring craniofacial gene TWIST1 [ 40 ]. Deletion of TWIST1 enhancers within the HDAC9 gene induced a small size skull in their mouse model, confirming the functional role of the regulatory region of the TWIST1 gene.…”
Section: Cnvs In Regulatory Regions Can Modulate Gene Expression Of O...mentioning
confidence: 99%
See 1 more Smart Citation
“…The major underlying pathogenic mechanism responsible for the craniofacial and limb anomalies observed in SCS patients is haploinsufficiency, usually caused by heterozygous variants affecting the coding region of the gene or structural variants, such as inversions or translocations encompassing TWIST1 regulatory elements, leading to functional loss of one gene copy ( Hyder et al, 2021 ; Hirsch et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%